If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2o(y + -7) + 16y = 8 + -5(70) Reorder the terms: 2o(-7 + y) + 16y = 8 + -5(70) (-7 * 2o + y * 2o) + 16y = 8 + -5(70) (-14o + 2oy) + 16y = 8 + -5(70) Multiply -5 * 70 -14o + 2oy + 16y = 8 + -350 Combine like terms: 8 + -350 = -342 -14o + 2oy + 16y = -342 Solving -14o + 2oy + 16y = -342 Solving for variable 'o'. Move all terms containing o to the left, all other terms to the right. Add '-16y' to each side of the equation. -14o + 2oy + 16y + -16y = -342 + -16y Combine like terms: 16y + -16y = 0 -14o + 2oy + 0 = -342 + -16y -14o + 2oy = -342 + -16y Reorder the terms: 342 + -14o + 2oy + 16y = -342 + -16y + 342 + 16y Reorder the terms: 342 + -14o + 2oy + 16y = -342 + 342 + -16y + 16y Combine like terms: -342 + 342 = 0 342 + -14o + 2oy + 16y = 0 + -16y + 16y 342 + -14o + 2oy + 16y = -16y + 16y Combine like terms: -16y + 16y = 0 342 + -14o + 2oy + 16y = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(171 + -7o + oy + 8y) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(171 + -7o + oy + 8y)' equal to zero and attempt to solve: Simplifying 171 + -7o + oy + 8y = 0 Solving 171 + -7o + oy + 8y = 0 Move all terms containing o to the left, all other terms to the right. Add '-171' to each side of the equation. 171 + -7o + oy + -171 + 8y = 0 + -171 Reorder the terms: 171 + -171 + -7o + oy + 8y = 0 + -171 Combine like terms: 171 + -171 = 0 0 + -7o + oy + 8y = 0 + -171 -7o + oy + 8y = 0 + -171 Combine like terms: 0 + -171 = -171 -7o + oy + 8y = -171 Add '-8y' to each side of the equation. -7o + oy + 8y + -8y = -171 + -8y Combine like terms: 8y + -8y = 0 -7o + oy + 0 = -171 + -8y -7o + oy = -171 + -8y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| F(x)=3a^2-3 | | 4x+12=10x+12 | | J+-3.1=10 | | 2/9n+.5=2/3(n+3) | | 48+4=k-6 | | 10y+50= | | 4x+20=14x | | 5c=120 | | j^2+jk-20k^2= | | -110+6m=-10-8m | | .5x-5=3/2x-5 | | 5x+6x=3x+2 | | 4x+4(10)=50 | | 5(4-2x)-(8x-12)=68 | | -2(4x)=2x | | 9=y+4x^2-8x | | 8k=13 | | 5(-4-2x)-(8x-12)=68 | | -183=-3(8b+5) | | x=7+-1y | | p-15p=11.01 | | 3(a-2)+6=5(a+4) | | 8x^2+4x-3x^2-2x+3= | | 9(x-1)-2(x-3)=4(x-1)+16 | | 2c+6=6c+30 | | 3x=9x-13 | | -9=-4g | | 6x+7y(2x)=20 | | 3.75+2(6.75)=7x+30 | | n(x^2+1)-3ln(x)=ln(2) | | (F-32)0.56=c | | -(3-1)=12-5-9 |